The Role of Corporate Governance as a Leverage Moderating and Free Cash Flow on Earnings Management - Reni Yendrawati; Erin Febriana Asy’ari (University of Merdeka Malang, 2017)
According to agency theory, there was a separation of function between principal and agent. This separation created different interest between principal and agent. This condition occurs because of the asymmetric information that the agent more knew company information than the principal. Therefore, it was interesting to study the actions of management. This research aimed to analyze the influence of leverage and free cash flow to earnings management and the ability to analyze the influence corporate governance consisting of managerial ownership, institutional ownership, independent commissioner, and audit committee in influencing earnings management on the listed manufacturing companies in Indonesia Stock Exchange during years 2010-2014. The results showed that leverage significantly influences to earnings management and free cash flow significantly influence to earnings management moderating variables that influence the relationship of leverage to earnings management is managerial ownership, independent commissioner, audit committee, and moderating variables that influence the relationship of free cash flow to earning management was managerial ownership and institutional ownership.DOI: https://doi.org/10.26905/jkdp.v21i3.704